Travel Time Cost for Private Car in Bumi Serpong Damai (BSD) City: Income and Mode Choice Approach - Resdiansyah Mansyur; Fredy Jhon Philip.S (WIDYAKALA: JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2017)
Abstract : Travel time cost is one of the primary aspects that considered, especially with respect to its economic impact. To account for the increment of road users, often travel time cost has to be highlighted and further investigated. One technique to compute travel time costs is by using travel time evaluation as a loss opportunity that used to produce traveling needs. The aim of the study is to compute travel time cost for the private transportation users in BSD City by employing two methodologies. Income approach is the first method, which requires only two factors to be computed (capital income and amount of annual working hour assuming that time used to produce one product as function of personal income). For mode choice approach, the method uses the travel time cost from the model to estimate the choices comparison from the specified mode traffic. In this model, comparisons of choices are assumed as a function of two independent variables; operational cost and time cost. Travel time cost is defined as the comparison between parameter of travel time cost against the operational cost. Additionally, the study adopted stated preference techniques surveys, which have been undertaken in BSD town area to derive the travel time cost. The survey focused on the private car passengers where background information collected were traveling distance, time of travel, journey characteristics, education level, employment and income of the respondents respectively. Subjects were asked to choose between different scenarios of mode choices. For income approach method, the results showed that the travel time cost for the private transport commuters was Rp 6,272 / hour/ person and Rp. 11,828 / hour / person by using mode choice approach. It was found that the value of time has increased as the income increases. Thus, value of time is significant in accounting for personal income.Keywords : Income, Mode Choice, Stated Preference